Razão autocrática: ideologia e direção política na progressividade da autocracia burguesa brasileira (1930-1945) - Sartoretto, Leonardo [UNESP] (2022)
This thesis investigates the existence of a theoretical-ideological body procedurally formulated in the work of Alberto Torres, Oliveira Vianna and Azevedo Amaral, in order to provide elements of an autocratic praxis for the direction of Brazilian capitalism. Assuming the existence of an evolutionary reason not reached in the Brazilian formation, these authors used a corroded reason, through a hard core located in positivism, to elaborate methodological approaches, historical investigations and political propositions that would offer the way for the resumption of such a path. Finding historical-concrete mediation in Getúlio Vargas, especially after the seizure of power by the Liberal Alliance in 1930, although already intertwined even before this political-military movement, the systematic set of representations elaborated by these intellectuals became an ideopolitical matrix, guiding the changes that took place during that period. Becoming an enlightened social subject and instrumentally rationalizing the concrete contradictions generated by the movement of big coffee capital, Vargas, an individual who condensed all these autocratic class demands in his political leadership, carried out an autocratic-progressive form of development for capitalism that is, it increased the internal productive forces without breaking with its excluding socio-political face, thus reaching its specific stage: the hyper-late industrialization. In this thesis, therefore, we seek to solve two distinct but closely related problems, which are both the demystification of the reductionist nature of this ideology, going to the root of its falsifying constitution, as well as exposing the main moments of the autocratic-progressive form of development. , following the influence of those previously conceived constructions, elaborated as responses to the arbitrarily manipulative demands of this autocracy.